Analisis Penerapan Hukum Islam terhadap Sistem Kerja Part Time: Studi Kasus Café Kota Medan - Nadzira putri Andani; Nikmah Dalimunthe (Economic Reviews Journal, 2024)
This study investigates how Islamic law is applied in the part-time work system in cafes in Medan City. Through a research approach consisting of direct observation, interviews, and document analysis, the study findings highlight various aspects, including the distribution of time, workers' rights and obligations, and fairness in salary payments. The results of the analysis show that the application of Islamic law in this context refers to the principles of ethics and justice, which play an important role in creating a work environment that is in accordance with religious values ​​and workers' needs. This research provides an important contribution to the understanding of how Islamic law can be implemented in business contexts such as cafes in metropolitan cities. By emphasizing the importance of paying attention to ethical values ​​and justice, this study provides a basis for developing work practices that are in accordance with the principles of Islamic law in a Muslim-majority society such as Medan City.